2018
DOI: 10.1038/s41467-018-05351-w
|View full text |Cite
|
Sign up to set email alerts
|

Immediate hydroxylation of arenes to phenols via V-containing all-silica ZSM-22 zeolite triggered non-radical mechanism

Abstract: Hydroxylation of arenes via activation of aromatic Csp2–H bond has attracted great attention for decades but remains a huge challenge. Herein, we achieve the ring hydroxylation of various arenes with stoichiometric hydrogen peroxide (H2O2) into the corresponding phenols on a robust heterogeneous catalyst series of V–Si–ZSM-22 (TON type vanadium silicalite zeolites) that is straightforward synthesized from an unusual ionic liquid involved dry-gel-conversion route. For benzene hydroxylation, the phenol yield is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…S11 and Table S2, entry 9 †). In addition, we found that the catalysis activity of Fe-TBAPy is comparable with that of the best-performing catalysts for benzene hydroxylation such as FeOCl (43.5%), 1 V-Si-ZSM-22 (30.8%), 3 TS-1 (29.5%), 54 (Table S3 †). The control experiment was further carried out to verify the heterogeneous nature of Fe-TBAPy.…”
Section: Catalytic Activitymentioning
confidence: 69%
See 1 more Smart Citation
“…S11 and Table S2, entry 9 †). In addition, we found that the catalysis activity of Fe-TBAPy is comparable with that of the best-performing catalysts for benzene hydroxylation such as FeOCl (43.5%), 1 V-Si-ZSM-22 (30.8%), 3 TS-1 (29.5%), 54 (Table S3 †). The control experiment was further carried out to verify the heterogeneous nature of Fe-TBAPy.…”
Section: Catalytic Activitymentioning
confidence: 69%
“…Currently, the global production of phenol is over 7.2 megatons per year. 1,2 Traditionally, phenol is produced from benzene by three-step cumene process, which suffers low yield ($5%), 3 high energy consumption, 4 and generates the explosive cumene hydroperoxide intermediate, 1 as well as the unnecessary by-products (e.g. acetone, a-methylstyrene).…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of excessive oxidation for gas‐phase oxidation resulting that carbon dioxide was the main product, which would cause both resource waste and greenhouse effect . Silicon‐based materials such as Fe‐SBA‐15, V–MCM‐41, Fe‐SiO 2 , Mn(TF5PP)‐MCM‐41 and V‐ZSM‐22 have been developed as catalysts for the liquid‐phase oxidation of naphthalene to prepare fine chemicals. But the catalysts preparation process was complicated and the reaction conditions were rigorous.…”
Section: Introductionmentioning
confidence: 99%
“…For achieving this goal, various oxidants such as H 2 O 2 , O 2 , N 2 O have been used . However, phenol is more activate than the substrate and can undergo over‐oxidation to producing the byproducts . Among the current oxidants and especially compared to O 2 as an eco‐friendly oxidant that needs a high temperature for its activation and N 2 O with limited source, H 2 O 2 is a promising choice because of easy handling and producing water as the only byproduct .…”
Section: Introductionmentioning
confidence: 99%
“…Among the current oxidants and especially compared to O 2 as an eco‐friendly oxidant that needs a high temperature for its activation and N 2 O with limited source, H 2 O 2 is a promising choice because of easy handling and producing water as the only byproduct . In the last decades, various catalysts based on noble and transition metals including Pd, Pt, Fe, Cu, Cr, and V were used for direct oxidation of benzene to phenol which vanadium based catalysts due to the intrinsic tendency of vanadium for oxidation of hydrocarbons have shown to be useful and promising catalysts …”
Section: Introductionmentioning
confidence: 99%